Anti‐Counterfeiting: Lanthanide "Chameleon" Multistage Anti‐Counterfeit Materials (Adv. Funct. Mater. 20/2017). (May 2017) - Kaczmarek, Anna M.; Liu, Ying‐Ya; Wang, Chunhua; Laforce, Brecht; Vincze, Laszlo; Van Der Voort, Pascal; Van Hecke, Kristof; Van Deun, Rik
Abstract : In article number1700258, Anna M. Kaczmarek, Rik Van Deun, and co‐workers describe hybrid materials displaying a multi‐stage security behavior, where a single material shows both wavelength‐ and temperature‐dependent luminescence properties. The materials consist of mixed lanthanide β‐diketonate complexes grafted into the pores of a nano‐sized metal organic framework (MOF), which show "chameleon" behavior.